ปัจจัยในการตัดสินใจซื้อที่อยู่อาศัย โครงการ Delight ในเครือ บริษัท พฤกษา เรียลเอสเตท จำกัด (มหาชน) ในเขตนนทบุรี - มาโท อโนทัย; ธำรงโชติ ณัฐชา (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2019)
The purposes of this study were to investigate customers’ personal characteristics, customers’ purchase decision, and associate customers’ purchase decision to their personal characteristics on buying housing from Delight Housing Project by Pruksa Real Estate Public Company Limited in Nonthaburi. The questionnaire was used to collect data from 218 customers who decided to purchase housing and already registered the mortgage. The statistics used to analyze the data included the frequency, percentage, mean, and standard deviation and tested the hypotheses with t-Test and F-Test at significance level of 0.05 The results revealed that the customers buying Delight Housing Project by Preuksa Real Estate Public Company Limited in Nonthaburi made decision on personnel first and followed by process, product, distribution channel, physical characteristics, and marketing promotion respectively. The hypothesis test showed that customers’ different genders and marital status were not different in terms of decision made to purchase Delight Housing Project by Preuksa Real Estate Public Company Limited in Nonthaburi. Therefore, the hypothesis set was rejected. It was found that the differences on customers’ age, education, occupation, monthly income affected the decision to buy Delight Housing Project by Preuksa Real Estate Public Company Limited in Nonthaburi; and the hypothesis set was accepted.